(untitled) (Politeja, 2025)
PERMANENT STRUCTURED COOPERATION AND ENHANCED COOPERATION IN THE DYNAMICS OF INTEGRATION PROCESSES IN THE EU’S SECURITY AND DEFENCE SPHERE The 20s of XXI century is a time of intensifying European integration in security and defence. The dilemmas related to this process stand out from others due to their complexity, diverse political narratives in the Member States and relations between governments and supranational institutions. Hence, the evolution of the Common Security and Defence Policy and its adaptation to contemporary challenges becomes the axis of the integration dynamics. The article analyses the diverse approaches in the integration process in the discussed sphere, and the discussion is initiated by the conditions of creation, principles of functioning and the role of enhanced cooperation and permanent structured cooperation (PESCO). Both mechanisms are used to increase the EU’s potential in areas that remain the competence of the Member States. The analysis will allow us to answer whether PESCO has proven to be a necessary complement in security and defence in strengthening cooperation, and why the enhanced cooperation mechanism was considered insufficient. It is also essential to demonstrate the relationship between PESCO and the European Defence Fund.